Psychiatric advance directives and reduction of coercive crisis interventions - SWANSON, JEFFREY W. (2008)
BACKGROUND: Psychiatric advance directives are intended to enable self-determined treatment for patients who lose decisional capacity, and thus reduce the need for coercive interventions such as police transport, involuntary commitment, seclusion and restraints, and involuntary medications during mental health crises; whether PADs can help prevent the use of these interventions in practice is unknown. AIMS: This study examined whether completion of a Facilitated Psychiatric Advance Directive (F-PAD) was associated with reduced frequency of coercive crisis interventions. METHOD: The study prospectively compared a sample of PAD completers (n=147) to non-completers (n=92) on the frequency of any coercive interventions, with follow-up assessments at 6, 12, and 24 months. Repeated-measures multiple regression analysis was used to estimate the effect of PADs. Models controlled for relevant covariates including a propensity score for initial selection to PADs, baseline history of coercive interventions, concurrent global functioning and crisis episodes with decisional incapacity. RESULTS: F-PAD completion was associated with lower odds of coercive interventions (adjusted OR=0.50; 95% CI=0.26-0.96; p < 0.05). CONCLUSIONS: PADs may be an effective tool for reducing coercive interventions around incapacitating mental health crises. Less coercion should lead to greater autonomy and self-determination for people with severe mental illness.